Vācaspatimiśra's Tattvasamīkṣā : the earliest commentary on Maṇḍanamiśra's Brahmasiddhi - Vācaspatimiśra, active 976-1000 (Nepal Research Centre publications, 2006)
Critically edited text of classical commentary on Brahmasiddhi of Maṇḍanamiśra, treatise on Advaita ontology; includes exhaustive introduction; based on rare manuscript in National Archives, Kathmandu.